D-Tags Design by Combining Bluetooth Router, IoT, and Mobile Phone to Track Personal Items - Ardiansyah Al Farouq; Rizal Fathurrahman (ELKHA : Jurnal Teknik Elektro, 2023)
Losing personal items such as a wallet or room keys is disturbing. Problems arise when clues to find the item are lacking or even non-existent. Of one hundred-two people who filled out the questionnaire about how often losing their belongings, 76% had experienced it. Because of that, it must be hard to remember where the last they put the stuff. Therefore people need tools that can help them easily find their item with a transmitter and connect to a mobile phone. Previous research showed that the transmitter with a frequency system had a detection distance of only 5 meters. From this weakness, the authors propose the development of a tracking items device that combines an Internet of Things-based Bluetooth transmitter and receiver system approach called D-Tags by combining Bluetooth routers, IoT, and mobile phones. The system is designed for both indoor and outdoor areas. Bluetooth testing allows the device to detect items up to 7.43 meters without wall obstacles. The system provided location information such as Living Room or Bedroom and the coordinates when outside the room. Regarding time, a single detection item is faster in the range of 15.13 seconds to 15.60 seconds than searching for two things simultaneously. From the tracking radius of the outdoor area, the device can track items up to 31.8 meters from the last item's position. All information tracking history can be seen on the web application. The experiment results prove that D-Tags can be used to track items by indicating their location and with a relatively short search duration.